QUALITY OF JUICE AND WINE MADE OF GRAPE VARIETIES AROMATNY AND CABERNET SAUVIGNON AFTER TREATMENT OF VINES BY BIOPREATION AGROMAR - М. А. Лопухова; О. Б. Паузер; І. П. Якуба; М. М. Артюх (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2018)
Aim. The purpose of this work was to find out the effect of processing of grape plants by the biopreparation AgroMar on the quality of wine materials and wine of varieties Aromatny and Cabernet Sauvignon. Methods. The biopreparation "AgroMar" is a biophigicide made of Trichoderma lignorum, which has a triple biological spectrum of action: bio-protection, biostimulation and bio-fertilizer. The research was conducted in 2016–2017 in the vineyards and laboratory of physiology of the reproduction center National Scientific Center “V. Ye. Tairov Institute of Viticulture and Wine-making”. The field experiments were conducted on technical varieties Aromatny and Cabernet Sauvignon. During the growing season, the experimental vines were sprayed with a solution of AgroMar at the concentration of 0.3 l / 10 liters of water (fine spraying with a manual sprayer), four times. The harvest was carried out in the first decade of September. The sugar content of the grape juice was determined by Bertrand's method, acidity – by titrometric method. The wine is made on the basis of the winery of National Scientific Center V.E. Tairov Institute. The tasting evaluation of the quality of wine was carried out by the tasting commission of the V. E. Tairov Institute. The metal content was determined by the method of atomic absorption spectrophotometry. Results. It was shown that processing by AgroMar improves the quality of juice, namely, increasing the sugar content and reducing the acidity for 2 years in both varieties, both in the juice out of white grapes Aromatny and in red grapes Cabernet Sauvignon. AgroMar treatment improves the organoleptic quality of wine, such as color, flavor and aroma, which raise the tasting grade of white wine by 0.1 point, red – by 0.6 and 1.0 points in 2016 and 2017, respectively. Biopreparation increases iron and manganese content in the white wine from Aromatny grapes and red wine from Cabernet Sauvignon grapes, and also reduces the content of heavy metals zinc and copper up to two times. Conclusions. It can be argued that biopreparation AgroMar positively affects the quality of juice and wine, as well as improves the microelement composition of the wine.